Orchid bees (Hymenoptera: Apidae) of the Brazilian Atlantic Forest - Nemésio, André (Zootaxa, 2009)
A detailed synopsis of all the orchid-bee species known to occur in the Atlantic Forest Domain, eastern Brazil, is provided, including synonymy, complete type data, diagnoses, relevant data on biology and geographic distribution (with detailed localities of known occurrence of each species), colorful illustrations of onomatophores (“name-bearing type specimens”), and a list with the main references dealing with each species. Fifty-four species are recognized to occur in the Atlantic Forest Domain. Identification keys are presented for each genus and their species occurring in the Atlantic Forest. Euglossa carinilabris Dressler, 1982, Euglossa cyanaspis Moure, 1968, Eulaema (Eulaema) niveofasciata (Friese, 1899) and Exaerete lepeletieri Oliveira & Nemésio, 2003, considered junior synonyms of other species by different authors, are reinstated as valid species. A full discussion on the status of the four orchid-bee species described by Linnaeus is presented, as well as colorful illustrations of the four onomatophores. The two existing onomatophores of orchid bee species described by Fabricius are also illustrated and his Apis cingulata has been shown to be the species recently described as Eulaema (Apeulaema) pseudocingulata Oliveira, 2006, which, thus, becomes a junior synonym (syn. n.). Euglossa aratingae sp. n., Euglossa carolina sp. n., Euglossa nanomelanotricha sp. n., Euglossa roderici sp. n., Euglossa roubiki sp. n., Eulaema (Eulaema) atleticana sp. n., and Eulaema (Apeulaema) marcii sp. n. are described as new species. Neotypes are designated for Eufriesea violacea (Blanchard, 1840) and Exaerete frontalis (Guérin-Méneville, 1844). Some corrections concerning the repository institutions of some onomatophores of orchid bees were also made: Eufriesea auriceps (Friese, 1899) holotype has been listed as belonging to the US National Museum (Washington) or to the American Museum of Natural History (New York) but, in fact, it belongs to the Zoologisches Museum der Humboldt Universität (Berlin); the lectotype of Eufriesea aeneiventris (Mocsáry, 1896) has been listed as belonging to the Istituto e Museo di Zoologia, Universita di Torino (Turin), but it actually belongs to the Hungarian Museum of Natural History (Budapest). Publication dates of both Exaerete frontalis Guérin-Méneville and Exaerete smaragdina Guérin-Méneville have been listed as 1845 but, in fact, the actual date is 1844. Based on the known geographic distribution and abundance of each species in orchid-bee inventories, IUCN criteria were applied and three species are recommended to be included in future lists of threatened species in one of the IUCN categories of risk: Eufriesea brasilianorum (Friese, 1899) and Euglossa cognata Moure, 1970 are suggested to be listed as “vulnerable”, and Euglossa cyanocholora Moure, 1996 is suggested to be listed as “endangered”. A fully annotated check list of all known orchid bee species is also presented as an Appendix.